Polietina Schnabl & Dziedzicki (Diptera, Muscidae): description of the male of P. major Albuquerque and female of P. wulpi Couri & Carvalho - Nihei,Silvio Shigueo (2002)
Polietina Schnabl & Dziedzicki, 1911 (Diptera, Muscidae) is a New World genus of Muscini, which comprises 18 species. The male of P. major Albuquerque, 1956 and the female of P. wulpi Couri & Carvalho, 1997 are herein described and illustrated for the first time. New geographical localities are recorded for both species.